2014
DOI: 10.1371/journal.pone.0105194
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Completing TB Diagnosis in Yemen: Services Should Respond to Patients' Needs

Abstract: Objectives and BackgroundObtaining a diagnosis of tuberculosis (TB) is a prerequisite for accessing specific treatment, yet one third of estimated new cases are missed worldwide by National Programmes. This study investigated economic, geographical, socio-cultural and health system factors hindering adults' attendance and completion of the TB diagnostic process in Yemen, to inform interventions designed to improve patient access to services.MethodologyThe study employed a mixed methods design comprising a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…The low socioeconomic status of Yemen makes travel cost a major barrier to undergoing treatment. A recent study performed in Yemen reported that travel cost acted as a major constraint in the diagnosis and continued treatment of patients, particularly those living in rural areas . Similar deductions have been reported in earlier studies performed in other developing countries .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The low socioeconomic status of Yemen makes travel cost a major barrier to undergoing treatment. A recent study performed in Yemen reported that travel cost acted as a major constraint in the diagnosis and continued treatment of patients, particularly those living in rural areas . Similar deductions have been reported in earlier studies performed in other developing countries .…”
Section: Discussionsupporting
confidence: 78%
“…The results show that living in rural areas is a main risk factor associated with TB treatment defaulting. The majority of TB patients travel from rural areas to urban areas for proper diagnosis and treatment due to the shortage of laboratory and health facilities in rural areas . This high percentage of defaulters from rural areas can be due to the poor economic situation in these areas and the low education level of defaulters from these areas .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important proportion of these cases are missed because individuals with symptomatic TB fail to seek medical advice for various reasons. The nonspecific presentation of TB, an expectation that symptoms will improve spontaneously and factors such as widespread stigma and misunderstanding about TB can delay or prevent individuals from seeking health services [3], [4]. A further significant barrier to diagnosis is the high transport costs that may arise from multiple visits required for diagnosis [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The nonspecific presentation of TB, an expectation that symptoms will improve spontaneously and factors such as widespread stigma and misunderstanding about TB can delay or prevent individuals from seeking health services [3], [4]. A further significant barrier to diagnosis is the high transport costs that may arise from multiple visits required for diagnosis [3], [4]. Missed or delayed TB diagnoses may lead to poorer individual outcomes and prolonged transmission, and it limits the impact of TB control measures [5].…”
Section: Introductionmentioning
confidence: 99%